Ensaio farmacológico clínico com extrato das raízes do Panax ginseng C. A. Meyer no tratamento da fibromialgia. - Andrade, Alessandra Sousa Braz Caldas de (2009)
Fibromyalgia is a chronic painful syndrome that affects up to 5% of the population worldwide. It may be associated with sleep or mood disorders and fatigue, and progresses with functional disability. Its pathogenesis consists of disorders of central pain modulation, involvement of the descending inhibitory system and substance P hyperactivity. The drug most commonly used for treatment of this syndrome is amitriptyline, which leads to an improvement in up to 50% of cases. Patients are interested in trying alternative or complementary medicine for the treatment of fibromyalgia. Panax ginseng C.A. Meyer is an herb that has been used for hundreds of years in oriental medicine. Preclinical studies have confirmed the antinociceptive effect of its active metabolites (ginsenosides) on substance P-induced pain, demonstrating an ability to inhibit calcium channels in dorsal medullary neurons. Clinical trials have shown an improvement in quality of life and fatigue with the use of ginseng. The study had as objective to evaluate the therapeutic efficacy of the extract of P. ginseng roots in controlling pain, fatigue, sleep quality, anxiety and quality of life in fibromyalgia. Fifty-two women of 21-60 years of age, who fulfilled the inclusion criteria of the study, were selected. A randomized, double-blind, controlled clinical trial was carried out over 12 weeks to compare the effect of P. ginseng (100 mg/day) with amitriptyline (25 mg/day) and placebo. Variables evaluated were pain, fatigue, sleep quality and anxiety using a visual analogue scale (VAS); pain was evaluated using a tender points count and quality of life using the Fibromyalgia Impact Questionnaire (FIQ). The patients were evaluated at six follow-up visits and results were expressed as means ± standard error (SE) of the mean using analysis of variation (ANOVA) and Tukey s post-hoc test. Thirty-eight women with a mean age of 43 years concluded the study. There were no statistically significant differences between the three groups with respect to baseline characteristics. VAS revealed a reduction in pain in the ginseng group (p<0.0001) with an improvement ≥ 30% from the sixth week of treatment onwards, an improvement in fatigue (p<0.0001) with a reduction ≥ 25% on the sixth week and ≥ 40% on the ninth week; and an improvement in sleep (p=0.0003) with a reduction ≥ 40% in the frequency of this complaint by the 6th week of treatment. The VAS evaluation of pain, fatigue and sleep detected an improvement compared to baseline values; however, there was no statistically significant difference between the three groups. With respect to anxiety, an improvement occurred in the ginseng group compared to baseline (p<0.0001); however, amitriptyline treatment resulted in a significantly greater improvement (p<0.05). Ginseng reduced the number of tender points and improved patients quality of life, as evaluated by the FIQ, compared to baseline in both cases (p<0.0001); however, no difference was found between the groups. Treatment with ginseng resulted in an improvement in all the parameters evaluated compared to baseline; however, there was no difference between this group of patients and those using placebo and amitriptyline, and this one was more effective than placebo or ginseng in improving anxiety. The beneficial effect on all parameters evaluated suggests that further studies should be performed with larger sample sizes and/or higher doses of ginseng to evaluate this herb for future use as a complementary therapy for fibromyalgia.